2014
DOI: 10.1159/000360581
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Rhizotomy for Pain from Neoplastic Lumbosacral Plexopathy in Advanced Pelvic Cancer

Abstract: Background: Pain from neoplastic lumbosacral plexopathy is resistant to conventional pain treatment. According to a recent review of destructive procedures for cancer pain, only cordotomy has been reported to play an important role in the treatment of cancer pain. To date, the effectiveness of dorsal rhizotomy, which selectively interrupts pain transmission, has not been shown in neoplastic lumbosacral plexopathy. Objectives: The present study seeks to find out the effectiveness of selective dorsal rhizotomies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…The survival of patients with MPS is considered to be very short, as demonstrated by many previous studies, and the reported median survival duration was 5.5-10.7 months after diagnosis (2,4,19,23). In the present study, patients in cases 1 and 2 died at 8 and 7 months from the time of diagnosis, respectively.…”
Section: Literature Review and Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The survival of patients with MPS is considered to be very short, as demonstrated by many previous studies, and the reported median survival duration was 5.5-10.7 months after diagnosis (2,4,19,23). In the present study, patients in cases 1 and 2 died at 8 and 7 months from the time of diagnosis, respectively.…”
Section: Literature Review and Discussionsupporting
confidence: 68%
“…Recent studies have shown that rotation switching of opioids to methadone was effective for refractory neuropathic pain (6,20). Other studies reported the efficacy of intervention strategies, including epidural analgesia (9,19), injection from a psoas sheath catheter (21) or intrathecal catheter (19,22), and dorsal rhizotomy (23). Radiotherapy is occasionally adapted for both cancer-directed and palliative therapy, although its efficacy remains to be clarified (1,2,4,5).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Another surgical option is to open the lumbar dura and cut the dorsal roots to the pelvis. 69 For pelvic pain mainly on one side, the spinothalamic tract on the contralateral side of the spinal cord can be interrupted by an open surgical or percutaneous cordotomy. Cordotomy usually is performed only unilaterally because bilateral cordotomy has a high risk of permanent motor weakness.…”
Section: Neurolytic Procedures For Relief Of Severe or Refractory Painmentioning
confidence: 99%
“…8 Neural sacrifice usually is unavoidable. 127 More destructive procedures (e.g., limb amputations) are ineffective. 22 Survivin, a member of the inhibitor of apoptosis family that is highly expressed during embryogenesis and largely undetectable in normal adult tissue, is overexpressed in transformed cells, including human malignant NSTs, prompting clinical trials using antisurvivin strategies.…”
Section: Managementmentioning
confidence: 99%